Os desafios dos professores e as adaptações tecnológicas do ensino médio no Paraguai durante a pandemia - Riedi, André Luis Sotille (2021)
The global pandemic, known as COVID-19, has created a global confinement and quarantine scenario. In the field of education, the measures that Paraguay and the countries of the region have taken in the face of the pandemic relate to the suspension of classroom classes at all levels of education, which gave rise to the Emergency Remote Education that allowed temporary access to the teaching and learning process with the support of digital technologies. This led education professionals to adapt to the use of digital technological tools as mediators of the teaching and learning process. The objective of this research is to verify the technological adaptations from the perspective of the teacher(a)s in the high school of private schools of the state of Alto Paraná in Paraguay through the pandemic. The research approach was qualitative and, regarding the methodological procedures, it was characterized as a case study, the technique for primary data production was the application of a questionnaire, for the search of secondary data, a systematic review of the literature. The questionnaire was prepared on the Google Forms platform and the method used to reach the target audience was Snowball - or snowball. As a result of the familiarization of teachers(a)s with the use of technology in their practices before the pandemic, it is noticed that there is a lack of training in all levels of education regarding the use of technology. The practices adopted by schools during the pandemic, highlight: platforms for synchronous and asynchronous moments, online chat, social networks for tutorials, social networks through social networks (Facebook, Youtube), and other strategies. Regarding the technological adaptations and the objectives of the education plan in times of pandemic Tu Escuela en casa, Paraguay was one of the few countries to issue a national orientation for schools from the first moment of the pandemic period in which social isolation became necessary. The positive aspects of the adaptations include the development of own teaching resources by (a)s professore(a)s, and the digital management of tasks, as negative aspects the internet connection and the lack of willingness of students to use technology for educational purposes.